Outcome of Immediate Postpartum Intrauterine Contraceptive Device in Caesarean Versus Vaginal Insertion: A Comparative Study - Sadia, Haleema; Waheed, Gulfreen; Zahid, Nadia; Navid, Sana; Asif, Sidra (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare the outcome of immediate postpartum intrauterine contraceptive device in caesarean versus vaginal insertion. Study Design: Quasi experimental study. Place and Duration of Study: Department of Obstetrics and Gynecology, Avicenna hospital, Lahore Pakistan, from Oct 2024 to Mar 2025. Methodology: After meeting selection criteria 250 females were enrolled and were divided in two groups of 125 each. Group-A were those females, who had vaginal delivery. Group-B was those females, who had cesarean section. Females were counseled about post-partum intra uterine contraceptive device (PPIUCD), and a CuT-80A was placed intrauterine. Outcome of PPIUD was noted in both groups. Results: In this study the mean age of the participants was 29.64±6.51 years, among them, 56(22.4%) were nulliparous. After insertion of PPIUCD, Menstrual irregularities were observed in 40(32.0%) of those with vaginal delivery and 37(29.6%) of those with C-section delivery (p=0.681). Menorrhagia was reported in 40(32.0%) females with vaginal delivery compared to 11(8.8%) with C-section delivery (p<0.001). Fever occurred in 21(16.8%) vaginal delivery cases and 36(28.8%) C-section cases (p<0.001). Conclusion: Based on this study, we may conclude that there were no statistically significant differences in the outcomes of immediate post-partum intra uterine contraceptive device (PPIUCD) insertion between caesarean and vaginal deliveries, except for the occurrence of menorrhagia and fever.